Susceptibility to Vancomycin of Biofilm Producing Staphylococci Isolated from Tertiary Care Hospital of Nepal - Manandhar, Sarita; Tuladhar, Ratna; Shrestha, Raju; Lekhak, Sunil; Chaudhary, Mahesh; Prajapati, Krishna (Vitae, 2022)
BACKGROUND: Methicillin resistance and biofilm-producing Staphylococci are emerging as multidrug-resistant strains narrowing the efficacy of antimicrobial therapy. Although vancomycin is used as the drug of choice to treat such isolates, different studies worldwide have documented the emergence of strains that are intermediately susceptible or resistant to this antibiotic. OBJECTIVE: The study aimed to determine the minimum inhibitory concentration of vancomycin to methicillin-resistant and biofilm-producing staphylococci isolated from different clinical specimens. METHODS: 375 staphylococci isolated from different clinical specimens over one year were included in the study. Biofilm formation was determined by the Tissue culture plate method (TCP), and ica genes were identified by Polymerase Chain Reaction (PCR). Antibiotic susceptibility and methicillin resistance were done following Clinical and Laboratory Standards Institute (CLSI) guidelines. The minimum inhibitory concentration (MIC) of vancomycin in all isolates was determined by the agar dilution method. RESULTS: Among 375 Staphylococci studied, 43% and 57% represented S. aureus and Coagulase-Negative Staphylococci (CNS), respectively. The rate of Methicillin-Resistant S. aureus (MRSA) and Methicillin-Resistant Coagulase Negative Staphylococci (MRCNS) were 81.4% and 66.8% respectively and determined by the disc diffusion method. The most potential antibiotics were tetracycline and chloramphenicol showing sensitivity to more than 90% isolates. The Minimum Inhibitory Concentration (MIC) value of oxacillin for staphylococci ranged from 0.125-32 μg/ml. Oxacillin agar diffusion method showed 51.6% and 79.9% isolates as MRSA and MRCNS, respectively, revealing a very high percentage of S. aureus and CNS isolates as methicillin-resistant. All isolates had susceptible vancomycin MICs that ranged from 0.125-2 μg/ml. Two S. aureus isolated from Central Venous Catheter (CVC) and catheter specimens were detected with intermediate susceptibility to vancomycin. Similarly, three CNS isolated from blood, CVC, and wound/pus (w/p) were intermediately susceptible to vancomycin. Strong biofilm formation was observed in 22.1% of clinical isolates, and the ica gene was detected among 22.9% of isolates. Only one S. aureus detected as a biofilm producer by the TCP method was found to have intermediate susceptibility to vancomycin. CONCLUSIONS: The increment in vancomycin MIC among methicillin-resistant and biofilm-producing staphylococci is alarming. Strict control measures to prevent methicillin-resistant isolates spread and routine surveillance for vancomycin-resistant isolates must be incorporated in hospitals to prevent antimicrobial treatment failure.